Pengaruh Struktur Modal, Ukuran Perusahaan Terhadap Kualitas Laba : Investment Opportunity Set Sebagai Variabel Moderasi - Ramdani, Safier; Chandra, Dicky (DFAME Digital Financial Accounting Management Economics Journal, 2023)
The aim of this study is to find out the capital structure, company size, and investment opportunity set (IOS) as a moderation to the quality of profit in the food and beverage subsector companies listed on the Indonesian Stock Exchange (BEI) in 2017–2021. The method used in this research is a quantitative one. This research population is a sub-sector of food and beverage companies registered in the BEI from 2017 to 2021, with a sample of nine (nine) companies. The data type used is secondary data, with the data processing techniques being descriptive statistical analysis and double linear regression analysis.